Okapi, a “fantastinouï” magazine for pre-teens in the spirit of May '68 - Cécile Boulaire (Strenae)
In 1971, the group Bayard Press brought out a magazine called Okapi for 7 to 12 year-olds. From the first number that came out, what was striking was the way in which the magazine captured the new educational ambitions of the generation of ‘68. A new behavioural model for the new generation developed: accessing information, framing demands for change, taking action. Yet, within the magazine, this spirit of protest existed alongside other more outmoded narratives, especially as regards the gender divide between boys and girls. My question is this: how can such discrepancies be explained? How did 1968 radicalism impact the Catholic culture of a youth press that had been around for several decades?